If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5 + 3(6 + -1x) = 1 -5 + (6 * 3 + -1x * 3) = 1 -5 + (18 + -3x) = 1 Combine like terms: -5 + 18 = 13 13 + -3x = 1 Solving 13 + -3x = 1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + -3x = 1 + -13 Combine like terms: 13 + -13 = 0 0 + -3x = 1 + -13 -3x = 1 + -13 Combine like terms: 1 + -13 = -12 -3x = -12 Divide each side by '-3'. x = 4 Simplifying x = 4
| 4x*3=99+x | | 20x=.6 | | 10a+5b=450 | | -2(6p-5)+2p=8p-8 | | 2(0,3x-1)-0,6=4+0,1x | | 8+10y=9y-6 | | -16t^2+57=0 | | 17x=6x-22 | | 138-4x=32x+22 | | 10.5=3b-12.5 | | 4x+2x+96-22=88+4x | | 6-3x-5x-1=10 | | 4(3x-44)=4(2x-10) | | 4x^4-17x^2+18=0 | | 5x*3+17=69+2x | | -2(3x-4)+12=8 | | -16t^2+7.85t+57=0 | | 4-x-2-x=x | | 5x^2+4xy-12y^2=0 | | 4-x-2+x=x | | 189.028=2*3.14*r^2+2*3.14*r*2.7 | | 6a+8b=1500 | | 3t-6=2t+2 | | -3x+8=-1 | | (3x*7)=21 | | 4x+2+7x-19=180 | | 10x^2+8x^4= | | -16t+7.85t+107=0 | | -18=-6-3x | | 4=2(5-x) | | 5y-7-6y=-9 | | 3(3-x)+2x=8-2(x-1) |